The Teaching of Creative Writing by Communicative Approach - Milal, A. Dzo'ul; Fi’aunillah, Tristy Kartika; Nuristama, Ramadhina Ulfa (ICONELT, 2024)
Strategies to increase the effectiveness of language teaching are continuously sought, including that of creative writing. This paper suggests a possible approach to overcome that problem. Considering the characteristics of a communicative approach in language teaching, on the one hand, and the targeted objectives of creative writing instruction, on the other, it is believed that such an approach, when appropriately implemented in the classroom instructional process, would be appropriate to optimize the effectiveness of students’ learning of creative writing. For instance, classroom activities encouraging students to engage in real-life communication and interaction, such as role-playing or group discussions, can effectively teach creative writing. As a conceptual study, this paper was written based on the writers’ personal experiences and reflections during their careers of teaching English using a communicative approach. Their practical experiences tailored to their understanding of theoretical underpinnings were then expressed to suggest the classroom techniques of teaching creative writing using a communicative approach to be effectively implemented in the classroom as a part of the language teaching and learning process. As a subjective study, the contents of this paper are desirable to be tried and practiced by teachers and researchers to measure their effectiveness.